Allocation of cytoplasm to macromeres in embryos of annelids and molluscs is positively correlated with egg size. Issue 3 (9th May 2016) - Jones, Caleb; Stankowich, Theodore; Pernet, Bruno
SUMMARY: Evolutionary transitions between feeding and nonfeeding larval development have occurred many times in marine invertebrates, but the developmental changes underlying these frequent and ecologically important transitions are poorly known, especially in spiralians. We use phylogenetic comparative methods to test the hypothesis that evolutionary changes in egg size and larval nutritional mode are associated with parallel changes in allocation of cytoplasm to macromere cell lineages in diverse annelids and molluscs. Our analyses show that embryos of species with large eggs and nonfeeding larvae tend to allocate relatively more embryonic cytoplasm to macromeres at 3rd cleavage than do embryos of species with small eggs and feeding larvae. The association between egg size and allocation to macromeres in these spiralians may be driven by constraints associated with mitotic spindle positioning and size, or may be a result of "adaptation in cleavage" to maintain rapid cell cycles in micromeres, position yolk in cell lineages where it can be most efficiently used, or adjust allocation to ectoderm to accommodate changes in embryonic surface area/volume ratio.